Pengaruh Motivasi dan Kinerja Terhadap Produktivitas Kerja Karyawan Tata Usaha PT Perkebunan Nusantara VI Kayu Aro - Alvia Santoni (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
This study aimed to determine the effect of either simultaneously or partially, as well as where the most dominant variable affecting employee performance PT.Perkebunan Nusantara VI (Persero) Kayu Aro. Referring to the results of calculations where t count> t table or 3.476> 2.110, meaning that there is a significant relationship between work motivation to productivity. Variable performance of turns obtained tcount 3.573 with 0.002 significance level (α = 0.05> 0.002). Referring to the above calculation, can be determined as follows: where t count> t table or 3.573> 2.110, meaning that there is a significant relationship between performance of the Work Productivity of employees of PT. Nusantara Plantation VI Kayu Aro.Large Influence Work Motivation to Work Productivity of employees of PT. Nusantara Plantation VI Kayu Aro is of 41.5%, while the contribution of performance variables affect the labor productivity amounted to 42.9%. Large Work Motivation and Performance influence on employee productivity PT. Nusantara Plantation VI Kayu Aro together amounted to 47.8% while the remaining 52.2% can be explained by other causes.Keywords: Motivation, Performance, Work Productivity